Fostering Machine Learning and IoT for Blockchain Technology Smart Cities Applications, Volume 1 - Ahmad, Khaleel; Dulhare, Uma N.; Badar, Mohammad Sufian; Ahamed, Jameel; Rizvi, M. A. (Transactions on Computer Systems and Networks, 2025)
XIII, 387 p. 120 illus., 80 illus. in color.